Analysis of Trunk Rolling Performances by Mattress Mobility Detection System in Poststroke Patients: A Pilot Study. (3rd March 2016) - Chiang, Shang-Lin; Lin, Chia-Huei; Lin, Chueh-Ho; Lu, Liang-Hsuan; Chang, Shin-Tsu; Sung, Wen-Hsu; Wei, Shun-Hwa
Abstract : Purpose. The purpose of this study was to investigate the correlation of kinematic variables with quality of trunk control in poststroke patients. Methods. This cross-sectional study included stroke subjects with mild to moderate motor deficit corresponding to Brunnstrom stages 3-4. Trunk functional performance was measured using bed mobility monitor system. All tasks were repeated ten times for both directions in each subject. Outcome measurements included the movement time and displacement of center of pressure (CoP) from supine to side lying and returning. Results. The results revealed that a significant longer turning time was observed when turning from the paretic side toward the nonparetic side compared to the other direction, with an estimated mean difference of 0.427 sec (P = 0.005 ). We found a significant difference in the time of rolling back to supine position between two directions. The displacement of CoP in rolling back from side lying on the nonparetic side was smaller than that from the paretic side with an estimated mean difference of −0.797 cm (P = 0.023 ). Conclusions. The impaired trunk mobility was associated with increased movement time and decreased displacement of CoP in poststroke patients. Trunk rolling performance has potential in assessment of stroke patients.